Analysis of the primary drying stage of a one-dimensional freeze-drying model with moving boundary - Dimalanta, Theresa Lina Borja; Del Rosario, Ricardo C.H. (Quezon City Institute of Mathematics, College of Science, University of the Philippines Diliman, 2008)
The system of partial differential equations modeling the primary drying stage of the freeze-drying process is derived and analyzed. We first derive the equations modeling the temperature in the freeze-dried region, the temperature in the frozen region, the concentration of sorbed water in the freeze-dried region, and the partial pressure of sorbed water in the freeze dried region.
Thesis (Ph.D. Mathematics)--University of the Philippines Diliman
Keywords: Freeze-drying.